The Light Emitter of the 2‐Coumaranone Chemiluminescence: Theoretical and Experimental Elucidation of a Possible Model for Bioluminescent Systems. Issue 4 (12th January 2016) - Schramm, Stefan; Navizet, Isabelle; Naumov, Panče; Nath, Naba K.; Berraud‐Pache, Romain; Oesau, Pascal; Weiss, Dieter; Beckert, Rainer
Abstract: The bioluminescence reaction of many biological subspecies, most notably fireflies, forms dioxetanone derivatives as high‐energy intermediates. The thermal instability of dioxetanones complicates understanding of the transition from the ground state to the first excited state that leads to light emission. Herein, we report the reaction mechanism of 2‐coumaranones, synthetically accessible strongly chemiluminescent materials that mimic the bioluminescence reaction. The pathways of chemiexcitation and photorelaxation are clarified on the basis of synthetic evidence and spectrochemical as well as computational mechanistic analysis. Abstract : The reaction mechanism of 2‐coumaranones, a new class of synthetically accessible strongly chemiluminescent materials that mimic the bioluminescence reaction, is reported. The pathways of chemiexcitation and photorelaxation are clarified on the basis of synthetic evidence and spectrochemical and computational mechanistic analysis.